2002
DOI: 10.1523/jneurosci.22-04-01228.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Central Terminal Vanilloid Receptor-1 Receptors and αβ-Methylene-ATP-Sensitive P2X Receptors Reveals a Converged Synaptic Activity onto the Deep Dorsal Horn Neurons of the Spinal Cord

Abstract: Using a spinal cord slice preparation and patch-clamp recordings from spinal cord dorsal horn neurons, we examined excitatory and inhibitory circuits connecting to lamina V neurons after the activation of afferent central terminal vanilloid receptor-1 (VR1) receptors and P2X receptors. We found that single neurons in lamina V often received excitatory inputs from two chemically defined afferent pathways. One of these pathways was polysynaptic from capsaicin-sensitive afferent terminals. In this pathway the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
62
3
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 55 publications
15
62
3
1
Order By: Relevance
“…The increases due to α, β-methylene ATP on inhibitory neurotransmission to CVNs was blocked by the P2X receptor antagonist TNP-ATP, further indicating facilitation of inhibitory neurotransmission to CVNs results from P2X but not P2Y receptors. This is congruent with the increased spontaneous IPSC frequency elicited by α, β-methylene ATP in lamina V neurons mediated by glycinergic/GABAergic inputs from dorsal horn interneurons (Nakatsuka et al, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…The increases due to α, β-methylene ATP on inhibitory neurotransmission to CVNs was blocked by the P2X receptor antagonist TNP-ATP, further indicating facilitation of inhibitory neurotransmission to CVNs results from P2X but not P2Y receptors. This is congruent with the increased spontaneous IPSC frequency elicited by α, β-methylene ATP in lamina V neurons mediated by glycinergic/GABAergic inputs from dorsal horn interneurons (Nakatsuka et al, 2002).…”
Section: Discussionsupporting
confidence: 76%
“…As the present and other studies have shown, the primary afferent neurons express both P2X 2 and P2X 3 receptors. In vitro studies in the spinal dorsal horn have show that the P2X receptor agonist α ,β-meATP causes an increase in glutamatergic (Nakatsuka and Gu, 2001;Nakatsuka et al, 2002;Nakatsuka et al, 2003;Tsuzuki et al, 2003). We have reported analogous results in the medullary dorsal horn (Jennings et al, 2006).…”
supporting
confidence: 71%
“…In the spinal somatosensory system, all P2X receptor subtypes with the exception of P2X 7 are expressed in the spinal dorsal horn, the dorsal root ganglion (DRG), and the central terminals of primary afferent neurons (Burnstock, 2000;Khakh, 2001;North, 2002). In vivo and in vitro electrophysiological recordings from single dorsal horn neurons have implicated P2X receptors on primary afferent terminals in spinal nociceptive transmission (Nakatsuka and Gu, 2001;Nakatsuka et al, 2002;Nakatsuka et al, 2003; Correspondence details: Dr. Ernest Jennings Dept. Anatomy & Cell Biology The University of Melbourne Parkville, Victoria, 3010, Australia Tel: +61 3 8344 5802 Fax: +61 3 9347 9619 Email: e.jennings@unimelb.edu.au.…”
Section: Introductionmentioning
confidence: 99%
“…One third or more dorsal root neurons, the source for those dorsal horn afferent terminals, respond to both CAP and ATP , although proportions vary across reports (Oh et al, 2001;Petruska et al, 2002;Labrakakis et al, 2003). Activation of P2X receptors in nearly all dorsal horn neurons transiently increases glutamate release , and most lamina II dorsal horn neurons are CAP sensitive (Nakatsuka et al, 2002). However, many P2X-sensitive afferent terminals in lamina V are CAP resistant .…”
Section: Vr1 and P2x Receptors Facilitate Glutamate Release Onto Diffmentioning
confidence: 99%